Analysis and Validation of medical Application through Electrical Impedance based System - Kumar, Ramesh; Kumar, Sharwan; Gupta, A. (International Journal of Intelligent Systems and Applications in Engineering, 2018)
This paper discussed the Design and implementation of the electrical impedance-based system, which covers both techniques (Impedance Plethysmography (IPG) and Electrical Impedance Tomography (EIT)). The electrical impedance distribution image of the cross section of a phantom based on current excitation and voltage measurement using electrodes pair is reconstructs image according to the electrical property of the medical phantom. The electrical impedance based image provides the significant morphological information. Image quality depends upon many other iterative process and image processing algorithms in addition to. The hardware designing of the system is a most important part for all impedance-based techniques. In measurement section, the current source of the electrical impedance-based system should supply multi-frequency signal for measurement because it provides more useful information about the phantom. Therefore, a signal source that provides accurate excitation and a reference signal for measurement are more useful. Matlab is used for image reconstruction and processing of the impedance data.